Portal vein wedge resection and patch venoplasty with autologous vein grafts for hepatobiliary–pancreatic cancer - Tadafumi Asaoka; Kenta Furukawa; Manabu Mikamori; Satoshi Hyuga; Tomofumi Ohashi; Iwamoto Kazuya; Yujiro Nakahara; Atsushi Naito; Hidekazu Takahashi; Jeongho Moon; Mitsunobu Imasato; Chu Matsuda; et al. (Surgical Case Reports, 2024)
Abstract Background Advanced hepatobiliary–pancreatic cancer often invades critical blood vessels, including the portal vein (PV) and hepatic artery. Resection with tumor-free resection margins is crucial to achieving a favorable prognosis in these patients. Herein, we present our cases and surgical techniques for PV wedge resection with patch venoplasty using autologous vein grafts during surgery for pancreatic ductal adenocarcinoma (PDAC) and perihilar cholangiocarcinoma (PhCC). Case presentation Case 1: 73-year-old female patient with PDAC; underwent subtotal stomach-preserving pancreatoduodenectomy, with superior mesenteric vein wedge resection and venoplasty with the right gonadal vein. Case 2: 67-year-old male patient with PDAC; underwent distal pancreatectomy and celiac axis resection, with PV wedge resection and venoplasty with the middle colic vein. Case 3: 51-year-old female patient with type IV PhCC; underwent left hepatectomy with caudate lobectomy and bile duct resection, with hilar PV wedge resection and venoplasty with the inferior mesenteric vein (IMV). Case 4: 69-year-old male patient with type IIIA PhCC; underwent right hepatopancreatoduodenectomy, with hilar PV resection and patch venoplasty with the IMV. All patients survived for over 12 months after the surgery, without local recurrence. Conclusions PV wedge resection and patch venoplasty is a useful technique for obtaining tumor-free margins in surgeries for hepatobiliary–pancreatic cancer.